An extensive swelling in the anterior mandible – A case report. (September 2017) - Kurien, Nikhil M.; Kumar, L.K. Surej; Uma, P.B.; Vivek, V.; Joseph, Anna P.
Abstract: Introduction: Glandular odontogenic cyst is a rare developmental odontogenic cyst, which often pose a challenge to diagnose it clinically. Presentation of a case: A 32 year old female patient was referred to the oral and maxillofacial surgery department with a chief complaint of a painless swelling in the anterior mandible, extending from mandibular left premolar to right first molar region, with fluctuancy and egg shell crackling at right premolar region. The associated teeth were firm. Radio graphically a large radiolucent lesion was seen extending from mandibular left premolar to right first molar region. Discussion: We had many differential diagnoses including keratocystic odontogenic tumour, ameloblastoma and radicular cyst. Incisional biopsy was taken from the most fluctuant area, which was histopathologically suggestive of glandular odontogenic cyst. Enucleation of the cyst, peripheral ostectomy, extraction of teeth and Carnoy's solution application were done under general anaesthesia. Conclusion: We often neglect to include uncommon lesions in the differential diagnosis, which may lead to inadequacy in the management protocol. Whenever possible, incisional biopsy should be performed to confirm the lesion before surgical enucleation. Here we present a case in which we were fortunate enough to diagnose the lesion by an incisional biopsy and managed according to the standard protocol. Highlights: GOC is an extremely rare, benign, cystic lesion of jaw with high rate of recurrence. Various differential diagnoses were present and we confirmed GOC by incisional biopsy. GOC has a definite histopathological criteria put forth by Kaplan. Managed according to proposed treatment protocol. We recommend incisional biopsy whenever possible to confirm lesion and modify treatment accordingly.